Effect of initial texture on the {10–12} twinning variants selection mechanism in AZ31 magnesium alloy - Hui Su; Zhibing Chu; Chun Xue; Yugui Li; Lifeng Ma (Materials Research Express, 2020)
The influence of the initial texture of the {10–12} twinning variants selection mechanism of the magnesium alloy was investigated using the compression test, the EBSD technology, the trace method, the orientation rotation method, and the Schmid’s law. Results show that various {10–12} twin patterns are observed in the AZ31 E90 sample subjected to compression. In the multi-twins inside a grain pattern, the high Schmid factor (SF) variant is activated first to coordinate the externally imposed strain, and the ortho-position (OP) variant with the best strain compatibility is activated. Typical case of paired twins in two neighboring grains usually have high SF, and the activation of corresponding variants follows the Schmid’s law. When E45 sample is compressed, the ${{\rm{SF}}}_{45^° }$ of a pair of relative variants among the six twin variants in the crystal is very large and favorable for local strong basal texture formed by the two adjacent grains for the twin-transfer phenomenon. When E0 sample is compressed, the activation of the corresponding variants follows the Schmid’s law and is linked to the stress fluctuation at the grain boundary.